HOLTER ECG MONITORING AND TREATMENT EFFECTIVENESS CONTROL IN PATIENTS AFTER MYOCARDIAL INFARCTION - U. A. Islamova; R. M. Gafurova; A. A. Abdullaev; I. A. Kadieva; Kh. M. Mutalipov (Российский кардиологический журнал)
In total, 316 patients after Q wave myocardial infarction (Q-MI) were randomised into 3 groups. For 6 months after discharge, the control group (n=103) received standard therapy (aspirin, enalapril, metoprolol, simvastatin). Group 1 (n=107) also received trimetazidine, and Group 2 (n=106) was administered ramipril, carvedilol, and trimetazidine. At baseline, 6 months and 2 years later, 24-hour Holter ECG monitoring was performed. The combination of ramipril, carvedilol, and trimetazidine (Group 2) was the most effective in prevention of pain and painless episodes of myocardial ischemia, as well as in reduction of supraventricular and ventricular extrasystolia incidence. The combination of enalapril, metoprolol, and trimetazidine (Group 1) was less effective than Group 2 treatment, but more effective than the therapy in the control group (enalapril, metoprolol, and standard therapy, without trimetazidine treatment).